Studies on Structural and Magnetic Properties in Co/Sm Multilayers - Erwin, Erwin (Jurnal Natur Indonesia, 2010)
Co/Sm multilayer films with structure of 20 [Co (x nm)/Sm (1.2 nm)] where x = 1.1, 2.2 and 4.2 nm and 20[Co (4.2nm)/Sm (x nm)] where x=1.2 nm to 7.5 nm were fabricated using dc magnetron sputtering. Each multilayer filmconsisted of 20 bilayers of Co layers with various thicknesses sandwiched with Sm layers. The application of lowangle X-ray diffraction measurements to the characterization of these multilayers is described. The periodiclayered structure with sharp interfaces was observed for all multilayer films. The measured magnetization valuesare lower than the values calculated in terms of the nominal concentration of cobalt in the multilayers. This impliessignificant “mixing” at small film thickness. The formation of a high magneto crystalline anisotropy of CoSm alloyat the interfaces, as a result of interdiffusion between Co and Sm layers was considered to be responsible for theincrease of the coercivity for Co/Sm multilayer.